The Effect of Distance Learning on Learning Outcomes of Children with Special Needs in Inclusive Schools in the New Normal - Nur Indah Sholikhati; Muhaimi Mughni Prayogo; Joko Santoso (Indonesian Journal of Disability Studies, 2021)
Distance education is an organized educational process that bridges the separation between students and educators mediated by the use of technology and minimal face-to-face meetings. Distance education evolved from correspondent education to education through e-learning across time and space. Currently, in Indonesia, even in all countries in the world there is an outbreak of Covid-19 which results in learning in the field of education having to change from face-to-face learning to distance learning. The purpose of this study was to determine how the effect of distance learning for children with special needs in inclusive schools in the new era of normality. The method used in this research is qualitative research with online interview data collection techniques, documentation, and literature studies related to children with special needs during the COVID 19 pandemic. Qualitative data analysis was carried out through the stages of data reduction, data presentation, concluding, and verification. Based on the purposive random sampling technique, this study involved 15 informants consisting of classroom teachers and Special Advisors from 12 inclusive schools in all districts in the Special Region of Yogyakarta. The results of the study revealed that distance learning which is applied in inclusive elementary schools in Yogyakarta is learning that is carried out online by utilizing various learning media both using the internet network and not Course materials are distributed online, communicated also carried out online, and all forms of examinations are also carried out online. The result of implementing distance learning in inclusive elementary schools is that learning the Indonesian language that is carried out remotely has a positive effect in the form of increased mastery of reading, listening, writing, and speaking competencies for children with special needs during the Covid-19 pandemic. The learning component that has the most influence is the selection of the learning media used. The more interactive the media used, the more effective the learning outcomes obtained by students. Even though online learning also encountered some obstacles, teachers continued to strive to improve the effectiveness of distance learning for children with special needs by collaborating with parents or guardians of students.